"Clubbing in the Club": Could Climate-Related Trade Arrangements Set the Pace for Future Climate Cooperation?. (18th July 2022) - Mbengue, Makane Moïse; Cima, Elena
Abstract : The climate is changing, and so is climate diplomacy. Global treaties may be failing, while unilateral actions are proving to be contentious both within the climate and the trade regime. At the same time, countries need to be given the right incentives to participate in the fight against climate change and to start curbing their emissions substantially. The European Union's (EU) decision to introduce a Carbon Border Adjustment Mechanism (CBAM) and the momentum around carbon pricing may be the perfect opportunity to revisit these ideas in the form of clubs . What if small groups of countries got together and set the pace for a new era in climate diplomacy? What if they relied on trade measures to do so? Clubs are not new in international law, let alone in international climate law. Compared to global approaches, they may avoid freeriding; compared to unilateral ones, they may reduce the risk of trade frictions. And not all major emitters need to participate right away. As few as two parties could start a climate club, a sort of club within the club, gradually catalyzing or influencing action on climate change. In this essay, we argue that climate clubs enable like-minded countries to assume more ambitious commitments and gradually pull in other countries with them.